INOVASI PRODUK, KREATIVITAS, ORIENTASI BERWIRAUSAHA, ORIENTASI PASAR, LOKASI DAN KEBERHASILAN USAHA - Muarrif Ardy; Donard Games; Dessy Kurnia Sari (Journal Publicuho, 2023)
This study aims to examine the entrepreneurial perspective on the success of catfish farming in Lima Puluh Kota District and Payakumbuh City. The research method uses descriptive quantitative analysis using data processing with the SPSS application and as enrichment using qualitative variables with 80 quantitative respondents and 5 qualitative respondents. The results of this study indicate that product innovation has a negative effect, creativity has a positive effect, entrepreneurial orientation has a positive effect, location has a negative impact, and market orientation has a positive effect on the success of catfish farming in Lima Puluh Kota District and Payakumbuh City. The limitations of this study are the use of product innovation variables, creative ability, entrepreneurial orientation, location, market orientation, and business success, and the sample used is very limited. It is recommended for further research to use other variables that have not been studied and increase the sample or even examine different types of businesses that are relevant to this research.